Return of large fin whale feeding aggregations to historical whaling grounds in the Southern Ocean - Helena Herr; Sacha Viquerat; Fredi Devas; Abigail Lees; Lucy Wells; Bertie Gregory; Ted Giffords; Dan Beecham; Bettina Meyer (Scientific Reports, 2022)
Abstract Fin whales (Balaenoptera physalus quoyi) of the Southern Hemisphere were brought to near extinction by twentieth century industrial whaling. For decades, they had all but disappeared from previously highly frequented feeding grounds in Antarctic waters. Our dedicated surveys now confirm their return to ancestral feeding grounds, gathering at the Antarctic Peninsula in large aggregations to feed. We report on the results of an abundance survey and present the first scientific documentation of large fin whale feeding aggregations at Elephant Island, Antarctica, including the first ever video documentation. We interpret high densities, re-establishment of historical behaviours and the return to ancestral feeding grounds as signs for a recovering population. Recovery of a large whale population has the potential to augment primary productivity at their feeding grounds through the effects of nutrient recycling, known as 'the whale pump'. The recovery of fin whales in that area could thus restore ecosystem functions crucial for atmospheric carbon regulation in the world's most important ocean region for the uptake of anthropogenic CO2.